1992
DOI: 10.3109/00498259209046653
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of albendazole and albendazole sulphoxide by ruminal and intestinal fluids of sheep and cattle

Abstract: 1. The metabolism of albendazole (ABZ), albendazole sulphoxide (ABZSO) and albendazole sulphone (ABZSO2) by ruminal, abomasal and ileal fluids of sheep and cattle was investigated under anaerobic conditions in vitro. 2. None of the compounds was metabolically changed by incubation with abomasal fluids of sheep and cattle. 3. ABZ and ABZSO were extensively metabolized by sheep and cattle ruminal and ileal fluids. ABZSO2 was unaffected by incubation with these gastrointestinal fluids. 4. The rate of ABZ oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 11 publications
1
41
0
1
Order By: Relevance
“…It has been shown that the gastrointestinal micro¯ora is very active in reductive biotransformation reactions of foreign compounds, particularly those containing sulphoxide groups (Renwick et al 1986). Sheep and cattle ruminal and intestinal contents sulphoreduce the BZDsulphoxide derivatives (ABZSO, oxfendazole) to form the respective thioethers (ABZ and fenbendazole) (Lanusse et al 1992;Virkel et al 1999). Xenobiotic metabolism in parasites seems to be predominantly reductive and hydrolytic (Douch and Buchanan 1979).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the gastrointestinal micro¯ora is very active in reductive biotransformation reactions of foreign compounds, particularly those containing sulphoxide groups (Renwick et al 1986). Sheep and cattle ruminal and intestinal contents sulphoreduce the BZDsulphoxide derivatives (ABZSO, oxfendazole) to form the respective thioethers (ABZ and fenbendazole) (Lanusse et al 1992;Virkel et al 1999). Xenobiotic metabolism in parasites seems to be predominantly reductive and hydrolytic (Douch and Buchanan 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the ratio of plasma area under curve (AUC) for ABZ-SO 2 /ABZ-SO obtained in cattle to be higher in comparison to sheep, after treatment with NETO [60][61][62]. In addition, the elimination half-life and mean residence of the ABZ-SO metabolite were significantly longer in sheep compared to cattle [73]. The bioavailability of OFZ and its metabolites after oral administration was significantly lower in goats than in sheep [74,75].…”
Section: Animal Speciesmentioning
confidence: 95%
“…Hennessy et al [79] demonstrated that an increased rate of digesta passage through increased feed intake reduced bioavailability of OFZ and its metabolites in sheep. Lanusse et al [73] proposed that bacterial population in microflora can play an important role on biotransformation of benzimidazole drugs in the gasrointestinal tract. In particular, bacteria-mediated reduction of benzimidazole sulphoxides (OFZ and ABZ-SO) back to the parent drug (FBZ and ABZ), extending residence time of the active drug in the animal's body.…”
Section: Animal Husbandrymentioning
confidence: 99%
“…ABZ is oxidized to its sulphoxide (ABZSO) derivative, which may be further oxidized to form ABZ suiphone (ABZS0 2 ) in the liver (I). Furthermore, ABZSO may be reduced back to its parent thioether (ABZ) by the GI microflora of sheep and cattle (9). Additionally, the ABZSO derivative is commercially available as an anthelmintic product for sheep and cattle.…”
Section: Introductionmentioning
confidence: 99%